Insolvency within multinational enterprise groups - Mevorach, Irit. (Oxford : Oxford University Press, 2009)
The law relating to multinational enterprise groups is notoriously complex. This book provides the first detailed analysis of the case law, presenting a clear model for future developments.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Bankruptcy; International business enterprises -- Law and legislation